BACE: Blockchain-based Access Control at the Edge for Industrial Control Devices of Industry 4.0 - Garrocho, Charles Tim Batista; Oliveira, Karine Nogueira; Sena, David José; Cavalcanti, Carlos Frederico Marcelo da Cunha; Oliveira, Ricardo Augusto Rabelo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2021)
The Industrial Internet of Things is expected to attract significant investments for Industry 4.0. In this new environment, the blockchain has immediate potential in industrial applications, providing unchanging, traceable and auditable access control. However, recent work and present in blockchain literature are based on a cloud infrastructure that requires significant investments. Furthermore, due to the placement and distance of the cloud infrastructure to industrial control devices, such approaches present a communication latency that can compromise the strict deadlines for accessing and communicating with this device. In this context, this article presents a blockchain-based access control architecture, which is deployed directly to edge devices positioned close to devices that need access control. Performance assessments of the proposed approach were carried out in practice in an industrial mining environment. The results of this assessment demonstrate the feasibility of the proposal and its performance compared to cloud-based approaches.